Barriers to Practice of Pharmaceutical Care in a Tertiary Hospital in Nigeria - Amibor, K. C.; Agbese, B. O.; Mokwunye, C. (Asian Journal of Science and Applied Technology, 2022)
Pharmaceutical care continues to gain worldwide acceptance since its introduction over two decades ago. In Nigeria, a variety of forces is slowing down the implementation of pharmaceutical care in healthcare institutions. This study was carried out to determine the barriers to implementation of pharmaceutical care in a tertiary hospital in Nigeria. These were achieved through the use of a prospective, cross-sectional study using a structured, pretested and self-administered questionnaire to 55 hospital pharmacists in Asaba in July 2018. The four-part Questionnaire evaluated demographics of respondents, knowledge of and reasons for not implementing pharmaceutical care and willingness to practice pharmaceutical care if perceived barriers were removed. Data obtained were analyzed using SPSS Version 22. Descriptive and chi square statistics were obtained. A P-value of less than 0.05 was considered statistically significant. A total of 55 questionnaires were administered to hospital pharmacists practicing at the Federal Medical Centre, Asaba, in 2018. Fifty questionnaires were returned, giving a response rate of 90.9%. Majority (80.0%) were aged 21-30 years, there were more females (56.0%) than males, most were single (74.0%), a third (34.0%) were holders of the Doctor of Pharmacy degree, nearly half (42.0%) were in practice for less than one year. Barriers identified were difficulty in accessing patients clinical and laboratory data, lack of acceptance by physicians and nurses, lack of space, inadequate number of pharmacists, pharmaceutical care is not feasible without financial incentives, pharmaceutical care required too much time, lack of clinical knowledge, Pharmaceutical care required too much effort, and lack of communication skills. Analysis of sex versus respondents was significant for those who felt pharmaceutical care was not feasible without financial incentives. (c2 = 12.236, *P = 0.022) with female respondents taking the lead (56.0%). This study revealed barriers that are militating against the practice of pharmaceutical care in the study area. Concerted efforts to address these challenges that will involve the management of the hospital, update lectures, attitudinal change by pharmacists and introduction of remuneration for additional services rendered by pharmacists are recommended.